The Muallaf Nurturing: Between In Map And Fact - Sabian Sabian; Sadiani Sadiani; Zainap Hartati; Abdul Khair (Jurnal Ilmu Komunikasi, 2019)
The process of Muallaf mapping in West Kotawaringin, Lamandau,and Sukamara Regency in Central Kalimantan Province is very crucial andinteresting to be investigated. Some problems are the Muallaf motivation toembrace Islam and their religious activities. To maintain the existence ofmu'allaf to keep in Islam, effective coaching is needed. This study uses aqualitative approach to understand symbolic meanings and interpret Muallaf’sactions. Data were obtained from 18 informants in 3 districts; WestKotawaringin Barat, Lamandau, and Sukamara Regency and the triangulationsystem, as well as by observation and documentary. The findings revealed;Muallaf, are facing adversity in diversity, they get minimum concern fromrelevant ministries or agencies, Islamic organizations, and non-governmentalorganizations in Central Kalimantan. The reasons are: there is no extensionagent specifically devoted to Muallaf; extension agents or preachers of theMinistry of Religion have not been functional for Muallaf, limited funds toprovide coaching, geographical constraints, and the low structured datacollection for the existence of Muallaf, no precise record for each regency. Theprocess of coaching mapping is to picture of coaching done by competentparties. Being a Muallaf, in general, is due to marriage, one's desires, and thenit is indeed given guidance by Allah. However, the majority factor triggering ismarriage. Based on the facts and problems of the Muallaf existence in the threeregencies, an effective coaching innovation is needed.